(untitled) (Research, Society and Development, 2023)
This study aimed to evaluate the long term memory through electroencephalographic techniques. Were evaluated, in individuals from the human and exact sciences groups, during the following cognitive activities: task: 1 – MEMORIZING WORDS; 2 – REMEMBER THE WORDS OF ACTIVITY 1; 3 – MEMORIZING FIGURES; 4 REMEMBER THE FIGURES OF THE ACTIVITY 3. The gamma rhythm was recorded through the electroencephalogram (EEG), according to the 10-20 system. Thus, the tasks aimed to analyze the capacity for long-term memorization. EEG signals were monitored during the reading and response of the tasks and the means and standard deviation of the gamma rhythm were calculated. The statistical model was BioEstat 5.0, T test for paired samples (p<0.05), Mann-Witney non-parametric test - independent samples and Excel. The results of the intragroup and intergroup analysis in human and exact subjects showed a significant difference in processing brain, through the gamma rhythm, during activities. Individuals in the humanities area used the anterior left quadrant more, while individuals in the exact sciences area used the posterior right quadrant more, as evidenced in the tasks of memorizing pictures and evoking pictures. It seems that there is an association of the gamma rhythm with the states of greater activation of the cerebral cortex during the programming and execution of cognitive activities.